PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT PENERBIT ERLANGGA JAKARTA TIMUR - Suwanto, Suwanto (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The purpose of this research is to determine the influence of work motivation on employee performance, then to determine the influence of work discipline on employee performance, and to determine the influence of work motivation and work discipline on employee performance at PT Erlangga Publishers, East Jakarta. Both partially and simultaneously. This type of research is a descriptive associative approach with quantitative methods. The sampling technique used was a saturated sample method of 60 respondents. The data analysis techniques used are instrument validity test, instrument reliability test, classical assumption test, linear regression analysis, coefficient of determination analysis, correlation coefficient analysis, hypothesis testing, t test, and f test, with the SPSS version 26 application. The results of this research were obtained as a result, it is known that the significance value (Sig.) is 0.000 < 0.005 and the calculated t value is 16,278 > 2.001, so it can be concluded that H0 is rejected and H1 is accepted, which means there is a partial positive and significant influence between employee motivation and performance. Then, based on the results of the analysis, the results obtained show that the significance value (Sig.) is 0.000 < 0.005 and the calculated t value is 15,043 > 2.001, so it can be concluded that H0 is rejected and H2 is accepted, which means that there is a partial positive and significant influence between work discipline on employee performance. The results of the analysis obtained results, it is known that the significance value (Sig.) is 0.000 > 0.005 and the calculated f value is 167,180 > 2.770, so it can be concluded that H0 is rejected and H3 is accepted, which means that there is a simultaneous positive and significant influence between motivation and work discipline on employee performance in PT Erlangga Publishers, East Jakarta. With a correlation coefficient of 0.924 and a coefficient of determination of 0.854 (85.4%) and the results of the multiple linear regression equation Y = 1.633 + 0.564 (X1) + 0.408 (X2)